The Relationship between Sociodemographic Factors and Short Stature in Toddlers - Indah Wulandari; Zuhrotul Eka Yulis Anggraeni; Roza Riska Romadhoni; Putri Nofia Marta Wulandari; Nuril Alifia Damayanti; Trias Maharani; Nikmatur Rohmah (STIKES Adi Husada, 2023)
Stature is the human physical form or somatotypes. Stature is often associated with sociodemographic factors. However, now, further evidence is needed about this phenomenon, especially in the toddler population. This study aims to analyze the relationship between sociodemographic factors and short stature in toddlers. Cross-sectional study design. The population is 303 toddlers aged 12-60 months in Lojejer Wuluhan Jember Village, East Java. A total of 172 samples were taken by cluster sampling. Sociodemographic variables that were measured included: father's age, mother's age, father's education, mother's education, family income, under-five gender, and birth weight. Toddler stature dependent variable. Data collection techniques using observation and questionnaires. Data analysis using logistic regression. The results showed that the variables of family income, child's gender, and birth weight had a relationship with short stature in toddlers. The results of the modeling analysis showed that male sex (p 0.004, AOR 3.94, 95% CI 1.54 to 10.07) and birth weight (p <0.001, AOR 39.005, 95% CI 7.69 up to 197.63) have been shown to have a significant relationship with short stature in toddlers. Birth weight is an illustration of the nutritional status of toddlers during the intra-uterine period. This study concluded that male toddlers have a higher risk of experiencing short stature compared to female toddlers. Babies born with low birth weight are at risk of experiencing short stature compared to those with normal birth weight and more. Nutritional status at birth is the initial capital for children's growth in the Toddler period. Therefore, the government needs to establish stricter policies so that pregnant women get assurance of adequate nutritional intake for themselves and their babies. In addition, it is necessary to carry out further studies related to mediating variables related to gender and their effect on short stature.